Hubungan Kepuasan Kerja dengan Turnover Intention Karyawan di PT. X - Dewi, Ni Luh Putu Dea Risma (JURNAL PSIKOLOGI MANDALA, 2025)
This study aims to determine the relationship between job satisfaction and employee turnover intention at PT. X. This study used a quantitative correlational approach with data collection using a job satisfaction scale and a turnover intention scale. Both measurement tools have been retested to obtain reliability values of (0.963) and (0.973). This study applies a non-probability sampling method with purposive sampling. The sample in this study consists of non-managerial employees, for a total sample size of 43 people. The data analysis used in this study was Spearman's rank test with a correlation coefficient of -0.328. The results indicated that there was a negative relationship between job satisfaction and turnover intention. This condition showed that the higher the level of job satisfaction of employees, the lower the turnover intention of employees at PT.X. Another finding from this study was the presence of a coefficient of determination of 10.76%. This value indicates that job satisfaction contributes 10.76% to explaining turnover intentions.